PENGARUH KEMAMPUAN DAN LINGKUNGAN TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KOTA SEMARANG - Yoen Enno Hapsari; Susi Sulandari (Journal of Public Policy and Management Review, 2019)
A good performance must have many criteria such as responsibility, quality, honestly, need for supervisional, productivity, and good sense of time. Based on Undang-undang number 5 year 2014 about Aparatur Sipil Negara Human resources especially on this case is state civil apparatus are being requested to do giving prime services. Prime services for society mean state civil apparatus are giving their best services. Including in this research is Bappeda Semarang City. The purpose from this research to knowing and analyzes employee performance, influence of ability to employee performance, influence of enivironment to employee performance, and than relationship of ability and environment to employee performance in Bappeda Semarang City. This research using quantity eksplanatif methodology. Amount of sample is 59 employee. Taking data using questioner. The research result is, employee performance in Bappeda Semarang City is good. There is positive strong enough correlation between ability to employee performance, enivironment to employee performance, and then ability and environment to employee performance in Bappeda Semarang City, proven with correlation kendall calculation and konkordansi kendall correlation. Employee performance needs to be improve with improving ability and environment.